Voltammetry - Spanning the kinetic timescale - Alden, J; Compton, R (2000)
Even nonspecialists can now use electrochemical technique to determine reaction rates for systems in which electron transfers are coupled to chemical reactions. J. A. Alden of Oxford GlycoSciences and R. G. Compton of Oxford University (both in the U.K.) show how simulated responses can be used to compare the range of rate constants that can be measured by various electrodes.